Atenuação de vibrações em máquinas rotativas flexíveis usando materiais viscoelásticos nos suportes - Saldarriaga, Manuel Ramón Villafañe (2007)
The purpose of this work is the study of a passive vibration control methodology applied to flexible rotors based on the use of viscoelastic vibration absorbers. In this way, the capability of the viscoelastic material to reduce mechanical vibrations is taken into account. A device composed by a set of viscoelastic absorbers is designed to be used in the supports of a flexible rotating machine. A methodology for the identification and model-updating of the flexible rotor, the viscoelastic absorbers, and the rotor-bearing-viscoelastic absorber system was performed. Two viscoelastic models were used in this work, namely the anelastic displacement fields (ADF) model and the complex modulus based model. The analytic response obtained by using the model composed by the flexible rotor and the viscoelastic absorbers was compared with the experimental one. The model allows the identification of the critical speeds observed in the experimental test. Experimentally, it was observed that the application of viscoelastic absorbers was able to reduce the initial vibration measured in the system, satisfactorily.